Pathways to reducing the negative impact of urban transport on climate change. Issue 1 (31st October 2022) - Seredynski, Marcin
Abstract: Transition to net zero greenhouse gas (GHG) emissions from urban transport requires strategies improving energy efficiency and contributing to energy conservation. Efficiency gains can be achieved via combination of new technologies, such as electrification, connectivity, and automation. Energy conservation focuses on reducing the total miles travelled by private cars. Supporting modal shift to public transport (PT) is the essential element of that strategy. It starts with policy support enabling time and space prioritisation of PT vehicles. Next, the emerging technologies can optimise performance and comfort of PT vehicles by making the best use of the assigned resources. This article shows how these technologies can reduce GHG emissions directly, as well as indirectly by making PT an attractive choice boosting patronage. A case study illustrating the improvement of the environmental performance of full hybrid buses via connectivity and geofencing is given. Abstract : Path to net zero emissions from urban transport goes via provision of attractive public transport (PT). It can be achieved by combining electrification, connectivity, automation and policy support enabling PT prioritisation over general traffic.